USING INQUIRY METHOD TO IMPROVE THE STUDENTSâ READING COMPREHENSION (A Classroom Action Research) - Burhanuddin, Wildhan (EXPOSURE JOURNAL, 2012)
This research aimed to explain the improvement of the studentsâ reading comprehension in terms of literal comprehension dealing with and word meaning main ideas and interpretive comprehension dealing conclusion. To explain the improvement, the researcher used a classroom action research (CAR) which was conducted in two cycles in which every cycle consisted of four meetings. The location of this research was taken at the first semester students of English Education Department with a number of the subject were 25 students. The research findings indicated that the application of Inquiry Method was significant in improving the studentsâ reading comprehension in terms of literal comprehension and interpretive comprehension. It was proved by the mean score of cycle I was 68, 47. It was classified as fair then improved to be 81, 20. It was classified as good in cycle II. They are higher than the mean score of diagnostic test namely 58.40 that classified as poor. Therefore there was the improvement of the studentsâ reading comprehension in terms of literal comprehension dealing with word meaning and main ideas and interpretive comprehension dealing conclusion.Keywords: Inquiry, Reading, Comprehension, Method.Penelitian ini bertujuan untuk menjelaskan peningkatan pemahaman membaca siswa dalam hal pemahaman literal dengan dan kata yang berarti ide-ide utama dan pemahaman interpretatif menyimpulkan kesimpulan. Untuk menjelaskan peningkatan, peneliti menggunakan penelitian tindakan kelas (PTK) yang dilakukan dalam dua siklus di mana setiap siklus terdiri dari empat pertemuan. Lokasi penelitian ini diambil pada mahasiswa semester I Jurusan Pendidikan Bahasa Inggris dengan sejumlah subjek 25 mahasiswa. Temuan penelitian menunjukkan bahwa penerapan metode Inquiry signifikan dalam meningkatkan pemahaman membaca mahasiswa dalam hal pemahaman literal dan pemahaman interpretatif. Hal itu dibuktikan dengan nilai rata-rata dari siklus I adalah 68, 47. Itu diklasifikasikan sebagai cukup kemudian ditingkatkan menjadi 81, 20. Hal itu tergolong baik pada siklus II. Mereka lebih tinggi dari nilai rata-rata dari tes diagnostik yaitu 58, 40 yang tergolong kurang. Oleh karena itu, ada peningkatan pemahaman membaca mahasiswa dalam hal pemahaman literal menyimpulkan dengan makna kata dan ide-ide utama dan pemahaman interpretatif menyimpulkan kesimpulan.Kata Kunci: Penyelidikan, Membaca, Pemahaman, Metode.